0084 Novel use of video and social media to obtain consent and provide information in a district general hospital. (2nd November 2015) - Elriedy, Mohamed; Harris, Patrick
Abstract : Background: Queen's Hospital Burton on Trent has a busy obstetric unit with around 3500 deliveries per year, 25% caesarean section rate and around the same rate for epidurals. After English the most common language spoken is Polish followed by Urdu, Punjabi and Hindi. Use of conventional translation services is inconvenient and unreliable. Methodology: Sharing of information before any procedure and obtaining consent may be seen as delivering education to a learner. To appeal to the widest learning styles (auditory, visual, kinesthetic) we have produced an multi-lingual multimedia package containing information to obtain consent for a variety of elective and emergency obstetric procedures. The information is presented either on Tablet or Online via Youtube and Twitter. In the preoperative clinic for elective caesarean sections, the patient and her birth partner are asked to watch a video either on a tablet or any handheld device they may have. It takes them through the whole perioperative journey explaining preoperative preparation, anaesthesia, recovery and postoperative analgesia. It also explains the associated risks. We also have content covering emergency LSCS and epidural analgesia. We have content in English, Urdu, Punjabi, Hindi and Arabic. This has led to standardisation of the content and the quality of information given. Patient satisfaction and feedback is measured by online survey. Outcomes and potential impact: Until now there has been no efficient way for non-English speaking patients to consent for anaesthesia for obstetric procedures in our hospital. To consent a patient, a patient needs to understand what type of anaesthesia she's going to have and what are the associated risks are. By using the AV material on a variety of platforms, the patient receives standardised high quality information appealing to all learning types. Taking the material online allows instant feedback and the ability to address any ongoing patient concerns. References: Hunt LM, de Voogd KB. Are good intentions good enough? Informed consent without trained interpreters. J Gen Intern Med. 2007;22(5):598–605 Schenker Y, et al . The impact of language barriers on documentation of informed consent at a hospital with on-site interpreter services. J Gen Intern Med. 2007;22(Suppl 2):294–9 Mason V, et al . The use of video information in obtaining consent for female sterilisation: a randomised study. BJOG. 2003;110(12):1062–71 Olver IN, et al . Improving informed consent to chemotherapy: a randomized controlled trial of written information versus an interactive multimedia CD-ROM. Patient Educ Couns. 2009;74(2):197–204